2011
DOI: 10.1200/jco.2010.32.5340
|View full text |Cite
|
Sign up to set email alerts
|

Shortening Infusion Time for High-Dose Methotrexate Alters Antileukemic Effects: A Randomized Prospective Clinical Trial

Abstract: A B S T R A C T PurposeTo determine whether shortening the infusion duration of high-dose methotrexate (HDMTX; 1 g/m 2 ) affects the in vivo accumulation of active methotrexate polyglutamates (MTXPG 1-7 ) in leukemia cells and whether this differs among major acute lymphoblastic leukemia (ALL) subtypes. MethodsFrom June 2000 through October 2007, 356 children with ALL were randomly assigned to receive initial single-agent treatment with HDMTX (1 g/m 2 ) as either a 24-hour infusion or a 4-hour infusion at two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 31 publications
2
44
0
Order By: Relevance
“…However, shortening of the methotrexate application time did not seem advisable, because in a randomized childhood ALL trial, shorter methotrexate application over 4 hours resulted in a lower event-free survival rate. 31 In Burkitt lymphoma, there was a significant difference in outcome for patients with an IPI score of 0-2 and those with an IPI score of $3 (P 5 .03). Also, female gender had a significant adverse influence on OS (P 5 .03), as observed in other Burkitt lymphoma studies.…”
Section: Discussionmentioning
confidence: 96%
“…However, shortening of the methotrexate application time did not seem advisable, because in a randomized childhood ALL trial, shorter methotrexate application over 4 hours resulted in a lower event-free survival rate. 31 In Burkitt lymphoma, there was a significant difference in outcome for patients with an IPI score of 0-2 and those with an IPI score of $3 (P 5 .03). Also, female gender had a significant adverse influence on OS (P 5 .03), as observed in other Burkitt lymphoma studies.…”
Section: Discussionmentioning
confidence: 96%
“…72 Although the optimal dosage and number of courses of high-dose methotrexate remain to be determined for individual subtypes of ALL, based on current evidence and pharmacologic studies in ALL subtypes, we recommend the infusion of high dose (ϳ 5 g/m 2 ) over 24 hours for T-cell cases and those with TCF3-PBX1 fusion. 69,73 For patients who PEDIATRIC ACUTE LYMPHOBLASTIC LEUKEMIA 1169 BLOOD, 9 AUGUST 2012 ⅐ VOLUME 120, NUMBER 6…”
Section: Selecting Effective Consolidation/intensification/ Reinductimentioning
confidence: 99%
“…Among different strategies of intensification of methotrexate, extended intravenous infusion (ie, over 24 hours) at high doses (eg, 5 g/m 2 ) has been widely used for patients with T-cell ALL. 69,70 Although the addition of escalating intravenous methotrexate (initial dose 100 mg/m 2 , increasing by 50 mg/m 2 every 10 days for 4 doses) without leucovorin rescue has been shown to improve the outcome of standard-risk ALL, 71 it was not as effective or less toxic than high-dose methotrexate with leucovorin rescue in a recent COG study for high-risk ALL. 72 Although the optimal dosage and number of courses of high-dose methotrexate remain to be determined for individual subtypes of ALL, based on current evidence and pharmacologic studies in ALL subtypes, we recommend the infusion of high dose (ϳ 5 g/m 2 ) over 24 hours for T-cell cases and those with TCF3-PBX1 fusion.…”
Section: Selecting Effective Consolidation/intensification/ Reinductimentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Mikkelsen et al 5 showed that a 1 g/m 2 dose given over 24 hours resulted in significantly greater active methotrexate polyglutamates in leukemic cells than the same dose given over 4 hours. In a randomized clinical trial, investigators from the Children's Oncology Group (COG) tested the efficacy and toxicity of a 2 g/m 2 dose over 4 hours versus a 1 g/m 2 dose over 24 hours.…”
Section: Introductionmentioning
confidence: 99%